OPTIMALISASI PROGRAM PRECEPTORSHIP DI RUANG RAWAT INAP RUMAH SAKIT MILITER DI JAKARTA - Kurniawan, Moh Heri; Hariyati, Rr Tutik Sri; Dewi, Laurentia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2019)
Preceptor has an important role in health services provided by new nurses who are in transition.Commitment of a predecessor is very important in the optimization of the discipline of theprogram. The purpose of the study is to identify, to give the workshop, and to evaluate thecommitment of the preceptorship program in the Military Hospital in Jakarta. This article used apilot study approach, implementing, and evaluation used literature review. Factor analysis usedfishbone diagram analysis. Samples used in the initial assessment were 10 inpatient rooms thatincluded 10 head nurses, 19 preceptors, and 36 preceptees. Implementation used a preceptorshipworkshop with 25 nurses to be prepared to be preceptor. The results of the examination indicate aproblem in the implementation of the program preceptorship on the presenter's order in theinpatient room. The evaluation results show 100% preceptor has a high commitment inperforming its role. The recommendation of this study is that preceptor commitment andoptimizing preceptorship program have to have policies, the flow of program development, andmonitoring and evaluation of program implementation in the inpatient room.